SISTEM INFORMASI GEOGRAFIS PASAR TRADISIONAL DI KABUPATEN KERINCI - Susanto, Darex; Sany, Ezrifal; Siary, Wiwin (FORTECH (Journal of Information Technology), 2023)
Geographic Information System (GIS) is a system that is made quite interactive and can integrate spatial data, this technology system technology can allow information about the distribution of traditional and modern markets in Kerinci district. The existence of a market in an area is able to improve the economy and regional income. in Kerinci regency there are many traditional markets spread across several sub-districts in Kerinci regency. Currently, information about the location of traditional markets is still very little and not much information about the market is presented in the form of digital maps, because of that, researchers aim to design and build a web-based Geographic Information System (GIS) application that can provide information about the location point of the nearest traditional market in Kerinci Regency. In this Traditional Market Geographic Information System (GIS) research, researchers used Qualitative methods with a Descriptive approach, descriptive research aims to make descriptive systematic, factual and accurate about the facts in a particular area with waterfall modeling as a Geographic Information system development methodology.